Clinico-radiological and functional outcome of Neer’s 2 part, 3 part and 4 part proximal humeral fractures in elderly treated by conservative management in a tertiary care centre of North India - Spolia, Pankaj; Ghani, Abdul (International Journal of Research in Orthopaedics, 2021)
Background: Treatment of proximal humeral fractures is challenging. Despite a rising incidence in proximal humeral fractures, there is still no evidence for the best treatment option, especially for the elderly patients. The aim of this prospective study was to evaluate the radiological in terms of union and functional outcome in terms of pain, range of motion of conservatively managed proximal humeral fractures in elderly patients. Methods: This was an observational prospective study of 35 patients aged above 65 years with proximal humeral fractures including 2 part, 3 part and 4 part based on Neer’s classification, treated by conservative method. Functional outcome was assessed by using Constant score at follow up of 1 year. Results: Out of 35 patients, 21(60%) were female and 14 (40%) were male with mean age of 76.8 (range 65 to 91years). On the basis of Neer’s classification, majority of patients (15, 42.8%) had 3 part fracture. Radiological union was achieved within 13 to 24 weeks, with an average of 18.4 weeks. Out of 35, 5 (14.3%) had excellent outcome, 8 (22.8%) had good functional outcome, 16 (45.7%) had moderate outcome, 6 (17.14%) had poor outcome. The results were comparable with the existing literature. Conclusion: In the present study, our data shows that the proximal humeral fractures can be effectively managed conservatively in the elderly patients. Two part fractures have best functional outcome and four part fractures have highest rate of complications.